The effects of internal and external economic variables on the Islamic banks' profitability in Malaysia / Mohamad Azwan Md Isa and Fakhrullah Ikram Baharudin. - Md Isa, Mohamad Azwan; Baharudin, Fakhrullah Ikram (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
The aim of this study is to examine the relationships and effects of bank-specific and economic variables on the profitability of eight Islamic Banks in Malaysia. The study uses 7-year annual panel data from 2012 to 2018. The profitability of the banks is tested using the banks' return on asset (ROA) whilst the economic variables are divided into two, namely banks' size, efficiency and financial risk that represent the bank-specific or internal variables, whereas the Gross Domestic Product (GDP), inflation rate and Kuala Lumpur Shariah Index (KLSI) represent the external or macroeconomic variables. The methods used to analyze the data consist of descriptive statistics analysis, Pearson's correlation analysis and multiple regression analysis. This study revealed that the five economic variables (banks' size, efficiency, financial risk, GDP and KLSI) have positive effects on the Islamic banks' profitability in Malaysia, whereas inflation rate poses negative effect. However, we noted that only the banks' efficiency, the GDP and KLSI have significant relationships with the Islamic banks' profitability in Malaysia. These finding are very beneficial to the related parties such as the Islamic banks' management and shareholders, investors of the Islamic stock market and the policy makers.